2020
DOI: 10.2147/ott.s237127
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nucleolar and Spindle Associated Protein 1 (NUSAP1) Promotes Bladder Cancer Progression Through the TGF-β Signaling Pathway</p>

Abstract: Purpose: NUSAP1 has been reported to be involved in the progression of several types of cancer. However, its expression and exact role in bladder cancer (BLCA) remains elusive. The aim of this study was to determine the expression and role of NUSAP1 in BLCA. Methods: Tissue microarray, real-time PCR, Western blot and immunohistochemistry assays were carried out to determine NUSAP1 expression in BLCA tissues and cells. The biological roles of NUSAP1 were investigated using CCK-8, EdU labeling, flow cytometry, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…22 In addition, the involvement of NUSAP1 in bladder cancer has been demonstrated on account of the effects of NUSAP1 knockdown or overexpression on cell proliferation, migration, invasiveness and chemosensitivity to gemcitabine by regulating the activation of TGF-β Signaling Pathway. 23 In the present study, we examined NUSAP1 expression in some osteosarcoma cell lines and discovered the upregulation of NUSAP1 in these cells compared with normal osteoblast cells, which consistent with previously published findings. However, we did not explore the expression of NUSAP1 gene in bone mesenchymal cells-derived tumor cells and we are exploring the expression and biological effects of NUSAP1 in bone mesenchymal cellsderived tumor cell lines and investigating the potential mechanism in our next study.…”
Section: Dovepresssupporting
confidence: 92%
“…22 In addition, the involvement of NUSAP1 in bladder cancer has been demonstrated on account of the effects of NUSAP1 knockdown or overexpression on cell proliferation, migration, invasiveness and chemosensitivity to gemcitabine by regulating the activation of TGF-β Signaling Pathway. 23 In the present study, we examined NUSAP1 expression in some osteosarcoma cell lines and discovered the upregulation of NUSAP1 in these cells compared with normal osteoblast cells, which consistent with previously published findings. However, we did not explore the expression of NUSAP1 gene in bone mesenchymal cells-derived tumor cells and we are exploring the expression and biological effects of NUSAP1 in bone mesenchymal cellsderived tumor cell lines and investigating the potential mechanism in our next study.…”
Section: Dovepresssupporting
confidence: 92%
“…For instance, in cervical cancer ( Li et al, 2019 ), NUSAP1 is shown to bound to the SUMO-E3 ligase Ran binding protein 2 (RanBP2) to induce the sumoylation of TCF4, thereby enhancing the Wnt/β signaling pathway and inducing tumor metastasis. Similarly, a high NUSAP1 expression level facilitated the development of bladder cancer by regulating epithelial-mesenchymal transition of bladder cancer via the TGF-β signaling pathway ( Gao S. et al, 2020 ). In addition, Liu ( Liu et al, 2018 ) reports that the mRNA and protein levels of NUSAP1 were more highly expressed in colon cancer than in paired non-cancerous adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar spindle-associated protein 1 (NuSAP1) is a microtubule-binding protein that participates in the regulation of mitotic progression and spindle formation and stability [13]. Recent studies have found that NuSAP1 was overexpressed in several types of cancers such as prostate cancer, colorectal cancer, and astrocytoma [14][15][16]. NuSAP1 also served as a key regulator of breast cancer progression, and it contributed to cell proliferation and invasion [17].…”
Section: Introductionmentioning
confidence: 99%